2019
DOI: 10.1002/ardp.201800314
|View full text |Cite
|
Sign up to set email alerts
|

Utility of anthranilic acid and diethylacetylenedicarboxylate for the synthesis of nitrogenous organo/organometallic compounds as urease inhibitors

Abstract: Fumarate diester 3 was synthesized upon reacting anthranilic acid with diethylacetylenedicarboxylate. Compound 3 was reacted with different nucleophiles in mild reaction conditions. Selected reaction routes that afforded products 6, 9, 10, 11, and 12 were explained. The estimated mechanism for the reaction of 3 with ethylenediamine to afford 9 was proved by X-ray single-crystal and retro-synthetic reaction. Acetyl anthranilic acid was utilized with zinc and copper to afford the organometallic compounds 14a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The two most common methods for the preparation of aminomaleimide derivatives involve the reactions of aryl- or alkylamines with diethylacetylenedicarboxylate 17,19 or 3-halomaleimides. 20 Approaches exploring the condensation between the corresponding amines and maleic anhydride 21 or tartaric acid 22 have also been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two most common methods for the preparation of aminomaleimide derivatives involve the reactions of aryl- or alkylamines with diethylacetylenedicarboxylate 17,19 or 3-halomaleimides. 20 Approaches exploring the condensation between the corresponding amines and maleic anhydride 21 or tartaric acid 22 have also been reported.…”
Section: Resultsmentioning
confidence: 99%
“…As for α-aminomaleimide derivatives specifically, the latter have been used recently, for instance, in the synthesis of functionalized N-heterocycles, 15 which act as a novel class of aggregation-induced emission (AIE) fluorophores 16 or promising potent urease inhibitors. 17,18 Thus, the development of novel pathways toward aminomaleimides with various structures is highly justified.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking simulations showed that the ionic ligands Cu-CP-1 and Cu-CP-2 were effective in blocking the urease activity pocket and thus inhibiting the urease function. 54,55 Both Cu-CP-1 and Cu-CP-2 were effective in binding to the urease active center. The effect of Cu-CP-1 was superior to that of Cu-CP-2, which is consistent with the results previously determined for the inhibitory activity.…”
Section: Molecular Dockingmentioning
confidence: 99%